Rediscovery of Oocephalus foliosus (Hyptidinae—Lamiaceae): notes on taxonomy and conservation of a species endemic to the campo rupestre of Central Brazil - Soares, Arthur De Souza; Negrão, Raquel; Harley, Raymond Mervyn; Pastore, José Floriano Barêa; Jardim, Jomar Gomes (Phytotaxa, 2021)
Oocephalus foliosus was described in the first half of 19th century, based on a collection from central Goiás state, Brazil, being collected again only three times in surrounding areas. Although this species seems to be rare and endemic to a narrow area, it has never been listed on any threatened list or had its conservation status assessed. Recently, we recorded a small population of O. foliosus in the Pireneus peak, an area of campo rupestre located in the municipality of Pirenópolis, Goiás, allowing us to improve the species description, assess its extinction risk and comment on its taxonomy. Also, a second step lectotypification was needed to the species and is here proposed.